Profil Kemahiran Berbahasa Inggris Mahasiswa Sebagai Prasyarat Kelulusan di Universitas - Nurdin Noni; Syarifuddin Dollah; Riny Jefri; Andi Anto Patak (Seminar Nasional LP2M UNM, 2019)
The objectives of the research are to get information about the profile of the students’ English proficiency level as a graduation requirement at the English study program and non-English study programs and the factors hampering the development of the students’ English proficiency. This research employed descriptive method involving 201 fifth semester students of S1 program. The instruments used were the English proficiency test (EPT) of diagnostic TOEFL and a questionnaire for students. The research result showed that the TOEFL mean scores were still very low compared to the required scores. For the students of English study program, the mean score gained was 468 of 500 and for students of non-English study program, the mean score was 370 of 450. The other finding was about the factors hampering the development of the students’ English proficiency. The factors include the students’ insufficient effort in learning and practicing English independently, the instructional English language which was not yet optimally used by the English lecturers, the students who very rarely attended English course/training, and the rare effort to familiarize the EPT (TOEFL) to the students. These factors should be considered by the policy makers if they expect that the students have good English proficiency as well as high global competitiveness..